Effect of Turmeric (Curcumin) Supplementation to Prevent Weight Loss in Type I Diabetic Rats (Journal of Fatima Jinnah Medical University, 2024)
Background: Curcuminoids in turmeric plants reduce the oxidative stress of diabetes and improve glucose utilization, so are helpful to prevent weight loss in diabetics. This study determined the weight loss-preventing effect of turmeric in type I diabetic rats and compared the groups.Subjects and methods: In this randomized controlled trial, alloxan was administered intraperitoneally to producetype-I diabetes. Forty-five albino rats were divided into control group A, diabetic group B and diabetic-treated group C with fifteen animals in each. Turmeric powder was given in a dosage of 300mg/kg body weight through oral gavage method to group C rats after induction of diabetes. Body weights of all rats were recorded by digital scale at baseline, end of 8th week and end of 12th week. Analysis of quantitative data (body weight) was done by using SPSS version 24, applying paired t-test and one-way ANOVA.Results: The average weight of the control group remained stable (mean weight 181 ± 16 g in the 12th week) and the weight change was not statistically significant (p-value = 0.393). The diabetic group showed a gradual decrease in body weight (mean weight 178 ± 18 g in the 12th week) which was statistically significant (p-value
Keywords: Type I Diabetes; Weight Loss; Alloxan; Turmeric Powder; Rats